Asian Financial Integration : Trends and Interruptions - Borensztein, Eduardo (IMF Working Papers; Working Paper ;, 2011)
The paper compares trends in financial integration within Asia with those in industrialized countries and other regional groups. Declines in cross-country dispersion in equity returns and interest rates suggest increased Asian integration, with the process interrupted by crises and global volatility. Cross-border equity and bond holdings have also increased, but Asian countries remain considerably more financially integrated with major countries outside the region than with those within the region. The paper also discusses whether potential benefits of regional financial integration, such as increased risk-sharing and stability of the investor base, have materialized.